Strengthening Türkiye’s drought management: insights from international practices (Netherlands, UK and USA) - Yilmaz, Ferhat; Osborn, Dan; Tsamados, Michel (Frontiers in Climate, 2025)
This paper provides an examination of drought management strategies in three countries: the Netherlands, the United Kingdom (UK), and the United States of America (USA). Additionally, it includes an evaluation of Türkiye’s approaches to water management and drought mitigation. Despite differing geographic, economic, and political conditions, these countries face similar challenges in drought management. Their approaches to dealing with drought have been examined from various perspectives, including institutional structures, legal frameworks, and operational strategies, with a focus on water allocation priorities, stakeholder collaboration, and the utilization of monitoring tools and data. The case studies revealed insights and experiences that can be used to evaluate and improve Türkiye’s existing water management and drought mitigation strategies. By drawing on the experiences of top-performing nations in drought management, this paper provides insights for creating a strong and sustainable water management for Türkiye, effectively tackling the challenges posed by climate change and ensuring the long-term security of water resources.